Digital public health leadership in the global fight for health security. Issue 2 (15th February 2023) - AlKnawy, Bandar; Kozlakidis, Zisis; Tarkoma, Sasu; Bates, David; Honkela, Antti; Crooks, George; Rhee, Kyu; McKillop, Mollie
Abstract : The COVID-19 pandemic highlighted the need to prioritise mature digital health and data governance at both national and supranational levels to guarantee future health security. The Riyadh Declaration on Digital Health was a call to action to create the infrastructure needed to share effective digital health evidence-based practices and high-quality, real-time data locally and globally to provide actionable information to more health systems and countries. The declaration proposed nine key recommendations for data and digital health that need to be adopted by the global health community to address future pandemics and health threats. Here, we expand on each recommendation and provide an evidence-based roadmap for their implementation. This policy document serves as a resource and toolkit that all stakeholders in digital health and disaster preparedness can follow to develop digital infrastructure and protocols in readiness for future health threats through robust digital public health leadership.